2021
DOI: 10.3390/biomedicines9080849
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Peptide—Drug Conjugate with DM1 for Treatment of FGFR2-Positive Tumors

Abstract: A maytansin derivative, DM1, is a promising therapeutic compound for treating tumors, but is also a highly poisonous substance with various side effects. For clinical expansion, we tried to develop novel peptide–drug conjugates (PDCs) with DM1. In the study, a one-bead one-compound (OBOC) platform was used to screen and identify a novel, highly stable, non-natural amino acid peptide targeting the tyrosine receptor FGFR2. Then, the identified peptide, named LLC2B, was conjugated with the cytotoxin DM1. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Compared with ADCs, SMDCs not only bind to the corresponding receptors on cancer cells efficiently but also diffuse more easily in tumor tissues due to their low molecular weight 30 . Next, we will discuss the application of different small molecular ligands in toxins delivery ( Table 2 ) 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 .…”
Section: Prodrugsmentioning
confidence: 99%
“…Compared with ADCs, SMDCs not only bind to the corresponding receptors on cancer cells efficiently but also diffuse more easily in tumor tissues due to their low molecular weight 30 . Next, we will discuss the application of different small molecular ligands in toxins delivery ( Table 2 ) 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 .…”
Section: Prodrugsmentioning
confidence: 99%
“…Lam et al report a synthetic peptide library to identify specific ligand-binding capabilities, which can be leveraged to target esophageal cancer cells. Wang et al describe that DM1, a promising chemotherapeutic that is also highly toxic, when combined with a peptide, LLC2B, inhibits tumor growth both in vitro and in vivo . While these PDCs are actively under investigation, there has been minimal work leveraging this technology for esophageal cancer.…”
Section: Novel Delivery Mechanismsmentioning
confidence: 99%
“…Payload is a cytotoxic compound and is divided into microtubule inhibitors, such as DM1, and DNA-damaging agents, such as anthracyclines (32). DM1 alone has not been developed as a drug but is currently used as an antibody-drug conjugate (33,34). It has been reported that the peptide LLC2B combined with DM1 exerts an anticancer effect in breast and esophageal squamous cell carcinoma, suggesting it could be developed as a potential PDC for tumor treatment (35).…”
Section: Introductionmentioning
confidence: 99%